2011
DOI: 10.1186/1742-6405-8-40
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and virologic failure after first-line NNRTI-based antiretroviral therapy in Thai HIV-infected children

Abstract: BackgroundThere are limited data of immunologic and virologic failure in Asian HIV-infected children using non-nucleoside reverse transcriptase inhibitor (NNRTI)-based highly active antiretroviral therapy (HAART). We examined the incidence rate of immunologic failure (IF) and virologic failure (VF) and the accuracy of using IF to predict VF in Thai HIV-infected children using first-line NNRTI-based HAART.MethodsAntiretroviral (ART)-naïve HIV-infected children from 2 prospective cohorts treated with NNRTI-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
32
2
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 22 publications
(35 reference statements)
13
32
2
4
Order By: Relevance
“…27 However, immunologic failure has a low sensitivity in detecting VF. 28 Predictors of VF in HIV-infected children reported in other studies include physician documentation of poor adherence, lower baseline CD4%, male gender, and treatment with nevirapine versus efavirenz-based HAART, and being an orphan. 25,26,29,30 In US children, reporting a barrier to adherence in the PACTG adherence questionnaire was significantly associated with elevated HIV-RNA.…”
Section: Discussionmentioning
confidence: 96%
“…27 However, immunologic failure has a low sensitivity in detecting VF. 28 Predictors of VF in HIV-infected children reported in other studies include physician documentation of poor adherence, lower baseline CD4%, male gender, and treatment with nevirapine versus efavirenz-based HAART, and being an orphan. 25,26,29,30 In US children, reporting a barrier to adherence in the PACTG adherence questionnaire was significantly associated with elevated HIV-RNA.…”
Section: Discussionmentioning
confidence: 96%
“…[1][2][3] Currently, HIV-infected children treated with highly active antiretroviral therapy (HAART) have increased life expectancy. [4][5][6] Deaths related to HIV/AIDS mortality have decreased significantly, but the non-AIDSrelated conditions maintain a stable trend in children living with HIV-1 after treatment with HAART. 7 Unlike many other chronic illnesses, children with HIV infection are more likely to experience more difficulties in their daily lives (e.g., parental death from AIDS and social stigmatization 8,9 ) which may worsen their QOL.…”
Section: Introductionmentioning
confidence: 99%
“…We identified 17 publications with data on children from a variety of settings which analysed either long-term virological patient outcomes 1,3,4,13,25 , durability of first-line ART 2,9,18,19,22 or response to second-line ART 8,23,24,[26][27][28][29] . Only two studies have reported outcomes following viral load rebound and the probability of switch or resuppression without switch in routine care 19,22 .…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Several papers report that within two years of first-line ART initiation, 33-38% of children experience virological failure; this varies with age and type of first-line ART [1][2][3][4] . This has raised concerns regarding the sustainability and long-term treatment options for children, who are recommended immediate ART from infancy and will require lifelong treatment but are faced with a limited range of antiretrovirals available in paediatric formulations 5,6 .…”
Section: Introductionmentioning
confidence: 99%